Effectiveness in the Removal of Endotoxins and Microbiological Profile in Primary Endodontic Infections Using 3 Different Instrumentation Systems: A Randomized Clinical Study - Cavalli, Daiana [UNESP]; Toia, Cássia Cestari [UNESP]; Flores Orozco, Esteban Isai [UNESP]; Khoury, Rayana Duarte [UNESP]; Cardoso, Flávia Goulart da Rosa [UNESP]; Alves, Marcelo Corrêa; Carvalho, Cláudio Antônio Talge [UNESP]; Valera, Marcia Carneiro [UNESP] (Elsevier, 2017)
Introduction This clinical study was conducted to correlate the microbiological profile and levels of endotoxins found in primary endodontic infection with the presence of clinical features and to evaluate the removal of microorganisms and endotoxins using rotary, reciprocating, and hybrid systems for biomechanical preparation. Methods Thirty single root canals with primary endodontic infection were evaluated with signs and symptoms and were randomly divided into 3 groups according to the instrumentation system used (n = 10) as follows: rotary Mtwo instruments (VDW, Munich, Germany) with 8 files, the reciprocating Reciproc system (VDW) with a single file, and Genius hybrid instruments with 3 files (1 rotary and 2 reciprocating files) with irrigation using 24 mL 2.5% sodium hypochlorite. Samples were collected before (S1) and after instrumentation (S2) before being submitted to microbiological culture (colony-forming units/mL) and the checkerboard DNA-DNA hybridization test. Endotoxins were quantified using the limulus amebocyte lysate assay. Results Microbiological culture showed statistical differences in the reduction of colony-forming units/mL with all systems tested (P <.05), but no statistical difference was found among the groups. The most frequently detected species were Capnocytophaga ochracea (53%) and Fusobacterium nucleatum (53%) at S1 and F. nucleatum (50%) and Leptotrichia buccalis (50%) at S2. As for the reduction of endotoxins at S2, Mtwo presented the best results (95.05%) followed by the Genius (91.85%) and Reciproc (64.68%) groups, but no statistical difference was found among the groups. Previous pain, tenderness to percussion, and presence of a sinus tract were associated with specific microorganisms (P <.05). Conclusions Signs and symptoms were correlated with microorganisms. Endodontic treatment was effective in reducing bacteria and endotoxins but was not capable of completely removing them from the root canal.
Keywords: Checkerboard DNA-DNA hybridization; instrumentation; primary endodontic infection